2022
DOI: 10.3389/feart.2022.864381
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Discharge Variability of the Doce River in SE Brazil During MIS 6 and 5

Abstract: The modern precipitation balance in southeastern (SE) Brazil is regulated by the South American summer Monsoon and threatened by global climate change. On glacial-interglacial timescales, monsoon intensity was strongly controlled by precession-forced changes in insolation. To date, relatively little is known about the spatiotemporal distribution of tropical precipitation in SE Brazil and the resulting variability of fluvial discharge on glacial-interglacial timescales. Here, we present X-ray diffraction-derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 61 publications
0
2
0
Order By: Relevance
“…The influence of sea level on the BIT index is clearly evident during Termination II, when the abrupt increase in sea level at ∼132 ka corresponds to a strong reduction of BIT values (Figure 4). In addition, clay mineral analyses of Core M125‐55‐7 indicate that precipitation in the densely vegetated low‐land catchment area of the Doce River was enhanced during late MIS 6 (Arndt et al., 2022; Hou et al., 2020a) which would also facilitate soil erosion and thus increase BIT values. Hence, a combination of sea level variations and run‐off changes in the hinterland may have caused the fluctuations in T TEX86_H .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of sea level on the BIT index is clearly evident during Termination II, when the abrupt increase in sea level at ∼132 ka corresponds to a strong reduction of BIT values (Figure 4). In addition, clay mineral analyses of Core M125‐55‐7 indicate that precipitation in the densely vegetated low‐land catchment area of the Doce River was enhanced during late MIS 6 (Arndt et al., 2022; Hou et al., 2020a) which would also facilitate soil erosion and thus increase BIT values. Hence, a combination of sea level variations and run‐off changes in the hinterland may have caused the fluctuations in T TEX86_H .…”
Section: Discussionmentioning
confidence: 99%
“…A particular motivation for this study derives from the fact that previous studies indicated unusually warm SST leading to the last two deglaciations (particularly during late MIS 6) implying an anomalous heat accumulation in the WTSA (Hou et al., 2020b; Santos et al., 2017). This pooling of warm surface waters is interpreted to have strongly impacted continental precipitation on South America by shifting the convection centers and enhancing coastal rainfall (Arndt et al., 2022; Hou et al., 2020a). However, since the available records were based on a single SST proxy, namely Mg/Ca analysis of G. ruber (p), the question remains if these warm temperatures might reflect a warm‐season bias of the Mg/Ca‐derived temperatures during this interval.…”
Section: Introductionmentioning
confidence: 99%